Is the Academic Medievalist Alone? - Kouky J. Fianu (The Ballad of the Lone Medievalist, 2018)
The trend towards a “shrinking past”1 is undoubtedly a reality that those of us working in American and Canadian universi-ties have known for many years now. Humanities disciplines, devoted more than others to the study of the past, have suffered inordinately from this situation. The result, one that we as me-dievalists know all too well, is that we end up being the sole departmental expert on the entire pre-1700 (mostly European) world. The reasons for this historiographical downsizing are complex: administrative proclamations of declining interest in the humanities in general are but one piece of the historical puz-zle. There is no need to enter into this debate here, though; what matters is the result. Where there used to be two, three or more medievalists, there is now barely one: a single soul who is often asked to also teach outside the period on more “relevant” issues. So, one it is. But does that make this sole specialist a lonely re-searcher? And is this a novelty?